Effects of potassium feldspar on slagging and fluxing in phosphorus produced via electric furnace. (3rd April 2017) - Geng, Ruixian; Xia, Jupei; Chen, Zhengjie; Yang, Jin; Zheng, Sen; Liu, Hailang
GRAPHICAL ABSTRACT: ABSTRACT: In this study, thermodynamic calculations were conducted to investigate K-feldspar fluxing yellow phosphorus produced via an electric furnace. The results demonstrated that the reaction temperature of K-feldspar as a flux was lower than that during the traditional process. The characteristic temperatures of silica-CaO and potassium feldspar-CaO systems under different mass ratios of SiO2 /CaO were measured according to the CaO-substituting decomposition products of phosphorus; the results showed that the temperature of the silica-CaO system was higher, 96.2–114.3°C, compared to the potassium feldspar-CaO system under the same conditions. These results indicate that K-feldspar as a flux in a phosphorus furnace can save energy and reduce cost. X-ray diffraction (XRD) analysis further revealed that a complex transition phase of silicates and aluminosilicates was accompanied by a conversion reaction of the silica-CaO and potassium feldspar-CaO systems, and that K2 O capable of co-producing potash fertilizer escaped as a gas through the collection equipment.